2018
DOI: 10.11607/ijp.5660
|View full text |Cite
|
Sign up to set email alerts
|

Prosthetic Tooth Replacement in a German Population Over the Course of 11 Years: Results of the Study of Health in Pomerania

Abstract: Similar age groups showed improvement in oral conditions. The proportion of higher-end restorations (FDPs and double crown-retained PRDPs), including the frequency of dental implants, increased.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
18
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(19 citation statements)
references
References 0 publications
1
18
0
Order By: Relevance
“…The risk of muscle tenderness is often found among individuals without occlusal support. Mundt et al 50 showed that Eichner class B4 and class C increased the risk of muscle tenderness 2.7–3.9 times more than class A. Similar findings have been reported by Nguyen et al 20 and Yekkalam and Wänman, 48 who concluded that total loss of bilateral occlusal support increases the risk for limited mouth opening (OR 2.2) and TMDs (OR 2.7).…”
Section: Discussionsupporting
confidence: 59%
See 2 more Smart Citations
“…The risk of muscle tenderness is often found among individuals without occlusal support. Mundt et al 50 showed that Eichner class B4 and class C increased the risk of muscle tenderness 2.7–3.9 times more than class A. Similar findings have been reported by Nguyen et al 20 and Yekkalam and Wänman, 48 who concluded that total loss of bilateral occlusal support increases the risk for limited mouth opening (OR 2.2) and TMDs (OR 2.7).…”
Section: Discussionsupporting
confidence: 59%
“…49 A reduced number of teeth was significantly associated with decreased mouth opening of less than 40 mm, TMJ tenderness and muscle tenderness, and a severe level of TMDs; 34,51 but it was not correlated with pain dysfunction syndrome, TMJ osseous changes and diagnosis classification of TMDs. 14,52,53 Loss of occlusal support resulted in muscle tenderness 50 but did not associate with TMJ sounds, TMJ dysfunction, or diagnosis classification of TMD. 20,32,38 Two articles indicated the effect of the position of the lost occlusal unit on TMDs (Table 4).…”
Section: Resultsmentioning
confidence: 94%
See 1 more Smart Citation
“…Tooth loss is no longer considered a natural phenomenon among older adults, and the demand for tooth replacement in this age group has increased over the recent decades. Prosthetic treatment is highly costly for public dental services as it involves providing dental rehabilitation procedures services and laboratory expenses [3][4][5][6][7]. Access to dental prosthesis treatment is usually hampered by the low availability of this procedure within public health care and due to the limited socioeconomic status of the population [8].…”
Section: Introductionmentioning
confidence: 99%
“…In prosthodontics, telescopic crowns are valid treatment options in cases of removable dentures on natural teeth or on implants. Doublecrown-retained removable partial dental prostheses were recently reported as having the highest increase in German elderly population (about 15% to 20%) [10], though good prognoses for conical crownretained removable partial dentures had also been reported in Kennedy Classes I, II, and III arches [11]. The most frequent complication of telescopic dentures was de-cementation of the primary crowns [12][13][14], which would be remediable in the context of long term studies emphasizing that patients' satisfaction mainly depended on the adequate retention of the double-crowns in time [15,16].…”
Section: Introductionmentioning
confidence: 99%